Islamic Economic Literacy Level Of Teacher In Al-Tsaqafah Islamic Bording School - nurul ichsan hasan (ITB AAS INDONESIA Surakarta, 2023)
The fundamental thing in supporting the development of Indonesia's sharia economy is to increase public literacy in the field of sharia economics. In Indonesia, the Financial Services Authority (OJK) is quite active in increasing the level of financial literacy of people from several age levels. In 2021, the Islamic economic literacy index in Indonesia will reach 20.01%. However, this figure shows that Islamic economic literacy in Indonesia is still at a low level. To increase the level of Islamic economic literacy in Indonesia, education and socialization are needed in the community, including Islamic boarding school teachers. Islamic boarding schools were targeted in an effort to increase the level of Islamic economic literacy due to a large number of about 28,194 and one of them was Al-Tsaqafah Islamic Boarding School. Based on this, it is necessary to conduct research first to determine the extent of the level of Islamic economic literacy owned by the teachers at Al-Tsaqafah Islamic Boarding School. This study uses the method developed by OJK and BI in measuring the level of Islamic economic literacy with quantitative survey analysis. The result is that the Islamic economic literacy of teachers at Al-Tsaqafah Islamic Boarding School is sufficient literate.